Development of Softbook Media for Learning the Value of Independence in Early Childhood Through Individual Learning at Home - Bilqis Nur Zaqia; Sa’dun Akbar; Imron Arifin; Irma Hirsjarvi; Asiye Zoghi (Tinta Emas Publisher, 2025)
Character education learning for children is more often done in schools through habits that are also continued at home, but different from 2020, precisely in mid-March, the Covid-19 pandemic occurred which required learning to be done entirely at home. This study focuses on producing soft book media that can stimulate Early Childhood Character Education that is appropriate (valid, practical and interesting) for individual learning at home. The study was conducted using the ADDIE model with qualitative methods in the form of observation and interview results. Interviews were conducted with students, accompanying teachers and the principal of TA Al Jabbar Malang. Data analysis used in this study used descriptive analysis, namely qualitative descriptive and quantitative descriptive in the form of: (a) Validity Level Data Analysis, (b) User Trial Data Analysis, (c) Media Effectiveness Level Data Analysis. The results of this study in the form of validation results obtained an overall average of 4.00. The final validation results are included in the valid criteria (satisfactory). This development has gone through a limited trial to determine the level of practicality of the textbook. The results of the limited trial obtained an overall average of 91.01%. The final result of the practicality level is included in the practical criteria. Thus, this softbook teaching media is worthy to be used for large-scale trials as a teaching media for learning the value of AUD independence. Suggestions submitted for further research are in the form of content.